The right question is
![x ^(2) -8x=20](https://img.qammunity.org/2020/formulas/history/middle-school/dl2wrb9uojxdq3v3tsokts7jt3ad2f2klb.png)
now multiply 1/2 by the coefficient of x which is 8
![(1)/(2) * 8=4](https://img.qammunity.org/2020/formulas/history/middle-school/i355c88i7o8jxwjuzjl6pw8p6bv6vp4kh2.png)
now add square of 4 on both side of equation we will get
![{x}^(2) -8x+ {4}^(2) =20+ {4}^(2)](https://img.qammunity.org/2020/formulas/history/middle-school/66eg0npd1rqhu02zapb2n577he1zs3k8jb.png)
![(x-4)^2=20+16](https://img.qammunity.org/2020/formulas/history/middle-school/7qs6u2mppzzmzwhxqp4a731gc7bfml5avz.png)
![(x-4)^2=36](https://img.qammunity.org/2020/formulas/history/middle-school/kb1741885042uetjjcpyzoljvls8u3h10l.png)
taking square root on both sides
we get
![(x-4)=-+6](https://img.qammunity.org/2020/formulas/history/middle-school/bp29yct3u636dwqkxalc2jszf3p52a0ll4.png)
![x-4=6, x-4=-6](https://img.qammunity.org/2020/formulas/history/middle-school/ow6qumw2zh6x0br2nlb1wr28t9l4v2ccub.png)
![x=6+4 , x=-6+4](https://img.qammunity.org/2020/formulas/history/middle-school/g3f47hg8ukl7vofjlz8pepbn1i6ssxvrz0.png)
![x=10,-2](https://img.qammunity.org/2020/formulas/history/middle-school/zdqbgh4gzuk0u2fq78emgy8a3uvwqcbhfw.png)
so third option is correct
if u find any confusion u can ask me
i hope you will understand it
Thank u